The Effect of the Ratio of Chili to Sugar on Sensory and Physichochemical Analysis of Crushed Catfish Jerky - Anni Faridah; Ranti Wahyuni; Riski Gusri Utami (Universitas Dr Soetomo, 2022)
Fish mashed jerky is a type of preserved food made from mashed fish meat, then added with spices such as sugar, coriander, galangal, salt, garlic, tamarind, onion, ginger and then molded and dried. Fish mashed beef jerky found in the market tastes sweet, and there is no addition of chili in the manufacture of minced fish jerky, while the people of Sumatra, especially the Minangkabau, like it spicy. Therefore, it is necessary to add additional spices that can add to the sweet taste of beef jerky by adding chilies to the manufacture of mashed fish jerky. This study aims to see the effect of the ratio of chili to sugar as much as 0:1, 1:0, 1:2, and 1:4 on the quality of shape, color, aroma, texture, and taste of jerky crushed catfish. This type of research is a pure experiment using a completely randomized design (CRD) method with three repetitions. The object of this research is jerky crushed catfish. The type of data is primary data sourced from 5 panelists who fill out the organoleptic test format. The data obtained were analyzed using statistical analysis (ANOVA), if Fcount > Ftable then continued with Duncan's test. The results of this study indicate that there is a significant effect of the chili to sugar ratio on the quality of color, texture, and taste (spicy). Meanwhile, on the quality of square and neat shape, fragrant aroma (typical of dried beef jerky) and taste (savory) there was no significant effect because Fcount < Ftable. The results of the quality test and the best hedonic (liking) of mashed catfish jerky were in the fourth treatment (X1) with a ratio of sugar to chili as much as 1:0 Keywords: Chili, Creamy Jerky, Catfish.